2015
DOI: 10.1038/srep17149
|View full text |Cite
|
Sign up to set email alerts
|

Increased risks between Interleukin-10 gene polymorphisms and haplotype and head and neck cancer: a meta-analysis

Abstract: Molecular epidemiological research suggests that interleukin-10 (IL-10) polymorphisms may be associated with an increased risk of head and neck cancer (HNC), but results remain controversial. To derive a more precise evaluation, we performed a meta-analysis focused on genetic polymorphisms of IL-10. PubMed, Embase, CNKI and Wanfang databases were searched for studies that examined the relationship between IL-10 polymorphisms or haplotypes and HNC risk. The odds ratio (OR) and 95% confidence interval (CI) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 48 publications
(64 reference statements)
0
48
1
Order By: Relevance
“…Quality assessment of included studies was evaluated with modified Newcastle-Ottawa scale (NOS) by two authors, and the scores ranged from 0 points (worst) to 9 points (best) (Table 3) [35]. …”
Section: Methodsmentioning
confidence: 99%
“…Quality assessment of included studies was evaluated with modified Newcastle-Ottawa scale (NOS) by two authors, and the scores ranged from 0 points (worst) to 9 points (best) (Table 3) [35]. …”
Section: Methodsmentioning
confidence: 99%
“…Two authors (HH and HW) independently performed quality assessment using quality scoring criteria20 based on criteria previously applied in observational studies for addressing genetic epidemiological issues, with the scores ranging from 0 points (worst) to 9 points (best) (Table S1). A study was classified as being of low quality when it scored <6 points.…”
Section: Methodsmentioning
confidence: 99%
“…30 IL-10 −819C/T SNP found to be associated with the risk of lung cancer, 31 urothelial bladder cancer, 32 and head and neck cancer. 23 IL-10 −592A/C was found to be associated with the risk of lung cancer, 31 non-Hodgkin's lymphoma, 33 and cervical cancer. 34 In breast cancer, studies conducted by Smith et al, 35 Kong et al, 36 and AlSuhaibani et al, 37 and meta-analysis 38 showed no association between IL-10 −1082A/G polymorphism and breast cancer incidence.…”
Section: Introductionmentioning
confidence: 94%
“…22 Polymorphisms in the IL-10 gene are found to play important role in cancer progression. Studies showed that IL-10 −1082A/G SNP was associated with poor prognosis of head and neck cancer, 23 oral cancer, 24 oral squamous cell, 25 cutaneous malignant melanoma, 26 prostate cancer, 27,28 digestive cancer, 29 and cervical carcinoma. 30 IL-10 −819C/T SNP found to be associated with the risk of lung cancer, 31 urothelial bladder cancer, 32 and head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%